Implementing a Sustainability Balanced Scorecard to Contribute to the Process of Organisational Legitimacy Assessment - Tairan Huang; Matthew Pepper; G. Bowrey (Australasian Accounting, Business and Finance Journal, 2014)
The purpose of this paper is to illustrate the use of a Sustainability Balanced Scorecard (SBSC) as a contributing factor in the process of organisational legitimacy assessment. The methodological approach in this study is supported by the application of content analysis to identify and examine the disclosed sustainability indicators of a major Australian financial institution (Westpac). The theoretical lens of legitimacy theory and the Balanced Scorecard (BSC) are used as points of reference to inform and structure the overall theoretical framework of this study. The results indicate that the four perspectives of a traditional BSC correlate with the main sources of influential inputs to Westpac’s sustainability reporting. In addition, the SBSC presented in this article successfully illustrates focal areas of reporting practice, providing a succinct overview of an organisation’s reporting activities. The primary contributions of this research are to the literature on social and environmental disclosures, including the research of Do, Tilt and Tilling (2007), and Baxter, Chua and Strong (2010) and the provision of a practical technique to illustrate the focal activity of an organisation’s social and environmental reporting as part of the legitimisation process.
Keywords: Balanced Scorecard; legitimacy; sustainability